Debris Flow Numerical Simulation Model Comparison with Field Events in Kuala Kubu Baru and Lentang, Malaysia - Kasim, Norhidayu; Abu Taib, K; Maturidi, A M A M; Wan Azahar, Wan Nur Aifa; Masjuki, Siti Aliyyah (IOP Publishing, 2021)
Debris flow is one of Malaysia's natural disasters which could cause casualties and serious infrastructure damage. Precisely predicting the factors associated with the occurrence of debris flow such as the run-out lengths, velocities and thickness of alluvial deposits can greatly mitigate damage, minimize or even avoid the aftermaths of the occurrence. Applying numerical simulation models explaining debris flow deposition would be a valuable tool in forecasting potential debris flow activity and providing criteria for designing protective measures. Comprehensive studies of available records of past debris flow events from relevant sources and site investigations have been carried out in order to assemble field information for the particular debris flow event in Malaysia. A number of calamitous debris flow events occurred in Malaysia have been closely observed and studied. The well-documented events, i.e. Lentang and Kuala Kubu Baru debris flow disasters occurred on 2nd November 2004 and 10th November 2003, respectively were simulated using the Kanako 2D (Ver.2.04) simulation model software. The results obtained from the numerical simulation model were compared with the real events in order to evaluate their predictive capabilities. The results showed an accuracy of more than 93% was obtained from the simulation model as compared to the real in-situ measurements. A positive simulation result will become a valuable method to predict potential debris flow hazard behavior of the same type and characteristics.